El hilo y la pluma: diversas perspectivas hacia el tejer de un texto poético - Śmiłek, Ewa (Collectanea Philologica, 2024)
Arachne, Penelope, Circe, Ariadne, and Moiras share the same attribute: the thread. These female figures from Greco-Roman mythology have become archetypes of women with the needle. The mythical spinners and their sewing have led to the coining of one of the obsessive metaphors of modern criticism: the relationship between the fabric and the literary text. We can observe it, especially, in contemporary poetry, in which the creation of the poetic texture – obvious is the metapoetic and self-referential background here – frequently constitutes one of the main themes. The objective of this article is to present different perspectives on the metaphorical role of mythological weavers as woman creating poetic text in the lyrical work of Aurora Luque (1962), Chantal Maillard (1951), and Sonia Bueno (1976).